1986
DOI: 10.1002/jobm.3620260902
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of some chemoautotrophic Chromatiaceae

Abstract: Isolation and characterization of some chemoautotrophic Chromatiaceae CHAHLUTTE: KAMPF and N. PFENNIG (Ileceived M a y 26, 1986) Three strains of facultatively chemoautotrophic Chromatiaceae were isolated from natural habitats under chemotrophic conditions and identified as Chromatium gracile (strains 23-3 and 25-1) and T h i o c~p~a roseopersicina (strain LABOE). The strains utilized hydrogen and reduced sulfur compounds for photo-and chemolithosutotrophic growth. Ammonium or dinitrogen were utilized as ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…T he rem a in ing 25% of thiosulfate th e re fo re serve as electro n d o n o r for th e red u ctio n o f C 0 2 into cell m aterial. T hese values are com p arab le to th o se d eterm in ed for ch em o lith o au to tro p h ically grow n thiobacilli [23] and facultatively aerobic C h ro m atiaceae [24,25], N o t only grow th yields b ut also grow th rates are red u ced u n d er sem iaerobic conditions. G row th rates of chem otrophically grow n cells w ere in the range of 0.015 t T 1 for T. roseopersicina strain M l to 0.027 h _ 1 for strain BBS and th e re fo re ab o u t 60% low er than those of p h o to tro p h ically grow n cells.…”
Section: R Esu Lts and Discussionmentioning
confidence: 90%
“…T he rem a in ing 25% of thiosulfate th e re fo re serve as electro n d o n o r for th e red u ctio n o f C 0 2 into cell m aterial. T hese values are com p arab le to th o se d eterm in ed for ch em o lith o au to tro p h ically grow n thiobacilli [23] and facultatively aerobic C h ro m atiaceae [24,25], N o t only grow th yields b ut also grow th rates are red u ced u n d er sem iaerobic conditions. G row th rates of chem otrophically grow n cells w ere in the range of 0.015 t T 1 for T. roseopersicina strain M l to 0.027 h _ 1 for strain BBS and th e re fo re ab o u t 60% low er than those of p h o to tro p h ically grow n cells.…”
Section: R Esu Lts and Discussionmentioning
confidence: 90%
“…While a light-stimulated uptake of NAHCO, was observed in all layers studied, the dark uptake was also high, suggesting the presence of significant chemoautotrophic activity in these mat layers. Chemolithoautotrophic growth in isolates of Chromatium gracile and Thiocapsa roseopersicina can be sustained by hydrogen and reduced sulfur compounds [20]. Since no attempt was made to exclude oxygen during the preparation and incubation of cells in the uptake studies and since 0.1 mM sulfide was included in the incubations, conditions were satisfactory to sustain chemolithoautotrophic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, growth of purple sulfur bacteria in the top layer appears not to be inhibited by the presence of oxygen during the day, despite the fact that bacteriochlorophyll a synthesis (BChla) is inhibited under these conditions [16][17][18][19]. It has been reported that T. roseopersicina has the capacity to grow chemotrophically in the presence of oxygen [18][19][20][21][22][23]. More importantly, T. roseopersicina is able to grow fully phototrophically with no more than 20% of the BChla present during continuous anoxic conditions [24,25].…”
Section: Introductionmentioning
confidence: 99%